Efficacy and safety of modified FLOT chemotherapy in gastric or gastroesophageal junction adenocarcinoma: a retrospective cohort study - Eslinger, Cody; Sahwan, Oudai; Jamal, Fares; Dias e Silva, Douglas; Buckner-Petty, Skye; Bauernfeind, Jennah; Ahn, Daniel; Borad, Mitesh J.; Wu, Christina; Zhu, Mojun; Wasif, Nabil; Starr, Jason; et al. (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Perioperative fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) is the standard treatment for resectable gastric and gastroesophageal junction (GEJ) adenocarcinoma, with fluorouracil administered at 2,600 mg/m2 as a 24-hour continuous infusion. However, toxicity can limit treatment delivery in routine practice. Dose-modified FLOT regimens are frequently used to improve tolerability, though data supporting clinical outcomes are limited. This study aimed to evaluate the safety, treatment delivery, and clinical outcomes of a predefined modified perioperative FLOT regimen in routine clinical practice.Methods: We conducted a retrospective cohort study of patients with resectable gastric or GEJ adenocarcinoma treated with predefined, modified perioperative FLOT at three institutions between 2019 and 2025. The regimen consisted of fluorouracil 2,400 mg/m2 over 46–48 hours, oxaliplatin 85 mg/m2, and docetaxel 40–50 mg/m2. Safety, treatment delivery, and clinical outcomes were assessed, with survival estimated using Kaplan-Meier methods.Results: Twenty-nine patients were included (median age 66 years; 62% male; 59% gastric and 34% GEJ tumors). Curative-intent resection was achieved in 86% of patients, with an R0 resection rate of 88% and a pathological complete response (pCR) rate of 16%. At a median follow-up of 30.3 months, median overall survival (OS) was 53.6 months (3-year OS 75.3%), and median recurrence-free survival (RFS) was 46.1 months (3-year RFS 52.4%). Grade 3 or higher neutropenia occurred in 34% of patients, and infections in 10%; no treatment-related deaths were observed.Conclusions: In this multi-institutional, real-world cohort, modified perioperative FLOT was associated with acceptable treatment delivery, manageable toxicity, and favorable clinical outcomes in selected patients with resectable gastric and GEJ adenocarcinoma. These findings support the feasibility of dose-modified FLOT in routine clinical practice, particularly for patients at risk for treatment-related toxicity.